The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.jtho.2021.01.106
|View full text |Cite
|
Sign up to set email alerts
|

FP07.06 Lung Immune Prognostic Index (LIPI) in Advanced NSCLC Patients Treated with Immunotherapy, Chemotherapy and both Combined Upfront.

Abstract: <0.001), and MBM-DT (0.32, <0.001) are the significant factors for prediction of ICI response, but others are not by multivariate analysis. Conclusion: Our results showed the superior value of the morphological biomarker for ICI response prediction, compared to PD-L1 IHC and TMB. The morphological biomarker can be a useful biomarker for clinical therapeutic decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In the context of combination therapy of chemotherapy accompanied with immunotherapy (and anti-angiogenics), this represents the first study to validate the LIPI in treatment-naïve patients. Our team recently reported similar results in a preliminary analysis of patient cohorts treated with immunotherapy and chemotherapy or an immunotherapy and immunotherapy association in the first-line setting [ 5 ].…”
Section: Lipi Is a Strong Prognostic Factor In Both Patients Treated With Immunotherapy In Combination With Chemotherapy And Also In Treamentioning
confidence: 66%
See 2 more Smart Citations
“…In the context of combination therapy of chemotherapy accompanied with immunotherapy (and anti-angiogenics), this represents the first study to validate the LIPI in treatment-naïve patients. Our team recently reported similar results in a preliminary analysis of patient cohorts treated with immunotherapy and chemotherapy or an immunotherapy and immunotherapy association in the first-line setting [ 5 ].…”
Section: Lipi Is a Strong Prognostic Factor In Both Patients Treated With Immunotherapy In Combination With Chemotherapy And Also In Treamentioning
confidence: 66%
“…To date, only tumor-related biomarkers are taken into account when choosing the patient’s treatment, with PD-L1 status being the most commonly used marker. As previously shown, the LIPI is independently associated with both survival and response under immunotherapy [ 5 ]. We consider it to be of very great importance to integrate host-related inflammatory markers into the algorithm containing tumor-related biomarkers in order to improve patient selection for immunotherapy therapeutic strategies for both monotherapy and combination therapy in NSCLC.…”
Section: Integrating Host-related Inflammatory Markers In Nsclc Will Improve the Selection Of Candidates For Each Therapymentioning
confidence: 95%
See 1 more Smart Citation
“…In our study, we defined fast progressors as patients with an OS < 3 months after ICI start. This is one of the aggressive progression patterns described in cancer patients under immunotherapy [23,26]. Although the immunological mechanisms have not been well established and this phenomenon remains controversial, some patients experience rapid and aggressive progression and previous reports highlighted inflammation as a key mechanism for the aggressive patterns [26,27].…”
Section: Discussionmentioning
confidence: 96%
“…This suggested that LIPI could be a useful tool to better identify true responders and, even more relevantly, to identify populations unlikely to respond to immunotherapy, providing additional information on outcome prediction, compared to the restricted vision, when using only tumor-based biomarkers. Similarly, LIPI, as for other host-related biomarkers, has also been explored in ≥50% PD-L1 NSCLC, another favorable population for immunotherapy [23]. In a cohort of 930 patients treated with ICIs, LIPI was an independent prognostic marker regardless of PD-L1 expression.…”
Section: Discussionmentioning
confidence: 99%